A Mission Divided - Close-Barry, Kirstie (ANU Press, 2016)
This book provides insight into the long process of decolonisation within the Methodist Overseas Missions of Australasia, a colonial institution that operated in the British colony of Fiji. The mission was a site of work for Europeans, Fijians and Indo-Fijians, but each community operated separately, as the mission was divided along ethnic lines in 1901. This book outlines the colonial concepts of race and culture, as well as antagonism over land and labour, that were used to justify this separation. Recounting the stories told by the mission's leadership, including missionaries and ministers, to its grassroots membership, this book draws on archival and ethnographic research to reveal the emergence of ethno-nationalisms in Fiji, the legacies of which are still being managed in the post-colonial state today. 'Analysing in part the story of her own ancestors, Kirstie Barry develops a fascinating account of the relationship between Christian proselytization and Pacific nationalism, showing how missionaries reinforced racial divisions between Fijian and Indo-Fijian even as they deplored them. Negotiating the intersections between evangelisation, anthropology and colonial governance, this is a book with resonance well beyond its Fijian setting.' - Professor Alan Lester, University of Sussex